Assembly and comparative analysis of the first complete mitochondrial genome of Salix psammophila, a good windbreak and sand fixation shrub - Qiao, Hongxia; Chen, Yajuan; Wang, Ruiping; Zhang, Wei; Zhang, Zhang; Yu, Fengqiang; Yang, Haifeng; Liu, Guiming; Zhang, Jiewei (Frontiers in Plant Science, 2024)
Salix psammophila, commonly known as the sandlive willow, is a vital shrub species within the Salicaceae family, particularly significant for its ecological role in regions susceptible to desertification and sandy soils. In this study, we assembled the complete S. psammophila mitochondrial genome using Pacbio HiFi third-generation sequencing data. The genome was found to be a typical single circular structure, with a total length of 715, 555 bp and a GC content of 44.89%. We annotated 33 unique protein-coding genes (PCGs), which included 24 core mitochondrial genes and 9 variable genes, as well as 18 tRNA genes (5 of which were multicopy genes), and 3 rRNA genes. Comparative analysis the PCGs from the mitochondrial genomes of S. psammophila, S. deltoides, P. simonii, S. wilsonii and S. suchowensis revealed that these genes are relatively conserved within the Salicaceae family, with variability primarily occurring in the ribosomal protein genes. The absence of the rps14, which encodes a ribosomal protein, may have played a role in the evolution of stress tolerance in Salicaceae plants. Additionally, we identified 232 SSRs, 19 tandem repeats sequences and 236 dispersed repeat sequences in the S. psammophila mitochondrial genome, with palindromic and forward repeats being the most abundant. The longest palindromic repeat measured 260 bp, While the longest forward repeat was 86,068 bp. Furthermore, 324 potential RNA editing sites were discovered, all involving C to U edits, with the nad4 having the highest number of edits. These findings provide valuable insights into the phylogenetic and genetic research of Salicaceae plants.